Evaluation of the effects of a dynamic culture on osteogenic differentiation of oral-periosteal cells grown on PLGA sponges - Ceccarelli, Gabriele; Benedetti, Laura; Graziano, Antonio; Alloni, Maurizio; Silvani, Giulia; Sampaolesi, Maurilio; Micheletti, Piero; Visai, Livia; Cusella De Angelis, Maria (Italian Journal of Anatomy and Embryology, 2015)
Oral-periosteum derived stem cells represent an innovative cell source for bone tissue engineering applications in terms of accessibility and self-commitment towards osteogenic lineage [1]. In this scenario, biomaterials play a pivotal role in tissue engineering in supporting stem cells growth and regeneration of tissue defects [2]. Among these biomaterials, Fisiograft®, a synthetic co-polymer composed of polylactic and polyglycholic acids produced by Ghimas (Bologna, Italy), is highly biocom- patible and completely absorbed within 4-6 months. In particular, Fisiograft® sponges are normally used in dental applications to fix completely periodontal defects without damage Schneider’s membrane. We evaluated the osteogenic potential of Fisiograft® sponges on oral-periosteal cells derived from patients undergoing dental extractions. For this purpose, we created a dynamic culture based on a rotating apparatus in which we seeded periosteal cells with Fisiograft® sponges for 7, 14 and 21 days without adding osteogenic supplement in the medium. Osteoblast differen- tiation of cells was evaluated by Alizarin Red S staining and by qRT-PCR on genes involved in bone development. Results show that Fisograft® sponges promote greater osteogenic differentiation of cells in the dynamic culture with respect to standard condition already at 14 days, as demonstrated by Alizarin Red staining. BMP-2 and Osteoprotegerin genes are highly expressed by cells grown on Fisiograft® sponges in dynamic culture at 14 days with respect to plastic culture. Taken together, these results confirm the osteogenic potential of Fisiograft® sponges in accelerating the dif- ferentiation of cells to an osteoblast phenotype (already to 14 days of culture) without any osteogenic induction. The combination of this PLGA biomaterial and oral-peri- osteal cells could represent a promising bio-complex in maxillo-facial tissue repair.